2004
DOI: 10.1128/mcb.24.22.10000-10015.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase 1c (ERK1c), a Novel 42-Kilodalton ERK, Demonstrates Unique Modes of Regulation, Localization, and Function

Abstract: Extracellular signal-regulated kinases (ERKs) are signaling molecules that regulate many cellular processes. We have previously identified an alternatively spliced 46-kDa form of ERK1 that is expressed in rats and mice and named ERK1b. Here we report that the same splicing event in humans and monkeys causes, due to sequence differences in the inserted introns, the production of an ERK isoform that migrates together with the 42-kDa ERK2. Because of the differences of this isoform from ERK1b, we named it ERK1c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 50 publications
2
70
0
1
Order By: Relevance
“…Similar ubiquitination-mediated activation of signaling components such as kinases and transcription factors has been reported in mammals and yeast (Muratani and Tansey, 2003;Aebersold et al, 2004). …”
Section: Mode Of Action Of Acre276 and Pub17 During Plant Defensementioning
confidence: 83%
“…Similar ubiquitination-mediated activation of signaling components such as kinases and transcription factors has been reported in mammals and yeast (Muratani and Tansey, 2003;Aebersold et al, 2004). …”
Section: Mode Of Action Of Acre276 and Pub17 During Plant Defensementioning
confidence: 83%
“…Thus, elucidation of the components by which different signals can be transmitted by similar signaling cascades is important. To date, there are two ERK genes (ERK1,2), and those encode two main proteins, p44 and p42 (19), and a few alternatively spliced forms such as the rodent ERK1b (21) and the primate ERK1c (22). We suggest that the major 50-kDa ERK that was observed in different mouse strains (SJL, BALB/c, and C57BL/6) after immunization with the myasthenogenic peptides or the TAChR and that was up-regulated by the dual APL may be an alternative spliced form of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…63 Interestingly, a similar splicing event also occurs in primates; in this case, however, the insert consists of 103 base pairs that are followed by a stop codon, which leads to the translation of a 42-kDa protein termed ERK1c. 40 It was shown that ERK1c is expressed in most human cells, is activated primarily by MEK1b, and is unique in regulating mitotic Golgi fragmentation. 62,64 Other ERK1/2 splice variants, such as ERK1d (unpublished) and ERK2b, 12 seem to be generated as well, and extend the specificity of the ERK1/2 cascade, as described below.…”
Section: Alternative Splicing Within the Erk1/2 Cascadementioning
confidence: 99%
“…Each gene encodes one main product, which are the primary 44-kDa (ERK1) and 42-kDa (ERK2) proteins. In addition, these genes encode several splice variants, including ERK1b (46 kDa 39 ), ERK1c (42 kDa 40 ), and others that will be described below. The MEK1/2-mediated phosphorylation of ERK1/2 on the Thr and Tyr residues in their Thr-Xaa-Tyr signature motif (Thr202 and Tyr204 in human ERK1 41 ) is the mechanism that induces their full activation.…”
Section: The Components Of the Erk1/2 Cascadementioning
confidence: 99%